Therapeutic and Prophylactic Effects of Amphotericin B Liposomes on Chronic Social Defeat Stress-Induced Behavioral Abnormalities in Mice - Lu, Jiashu; Huang, Chao; Lu, Qun; Lu, Xu (Frontiers in Pharmacology, 2022)
Recently, innate immune system stimulants, such as lipopolysaccharide (LPS) and macrophage-colony stimulating factor (M-CSF), were reported to prevent and reverse chronic stress-induced behavioral abnormalities, suggesting that innate immune stimulation could be a potential strategy for the treatment and prevention of mental disorders. Amphotericin B liposome is a clinically available antifungal medication that can stimulate macrophages and microglia. We hypothesize that amphotericin B liposome may be used to prevent and reverse behavioral abnormalities triggered by chronic stress. As expected, our results showed that a single injection of amphotericin B liposome (1 mg/kg) immediately after stress cessation reversed the decrease in time spent in the interaction zone in the social interaction test (SIT) and the increase in immobility time in the tail suspension test (TST) and forced swimming test (FST) in mice caused by chronic social defeat stress (CSDS). In addition, a single injection of amphotericin B liposomes (1 mg/kg) one day before stress exposure was found to prevent the CSDS-induced decrease in time spent in the interaction zone in the SIT and the increase in immobility time in the TST and FST in mice. Pretreatment with minocycline to inhibit the innate immune response was able to abolish the reversal effect of post-stress injection of amphotericin B liposomes on CSDS-induced behavioral abnormalities and the prophylactic effect of pre-stress injection of amphotericin B liposomes on CSDS-induced behavioral abnormalities. These results demonstrate that amphotericin B liposomes have both therapeutic and prophylactic effects on chronic stress-induced behavioral abnormalities in mice by mobilizing the innate immune response.